THE EFFECT OF MILKING TIME ON THE PRODUCTION OF ETAWA GOAT MILK AT RAKA ETAWA FARM, SINGAPADU, SUKAWATI SUB DISTRICT, GIANYAR REGENCY - Talitha Ad Hajina Br. Sitepu; I Made Sukada; Wayan Bebas (Buletin Veteriner Udayana, 2025)
Crossbred etawah goats are one of the ruminant livestock breeds with great potential as milk producers with high nutritional value. One of the important factors that can influence milk productivity is milking time. This study aims to determine the effect of milking time on the milk yield of crossbred etawah goats. This research employed a quantitative method with an experimental approach. The sample consisted of 15 crossbred etawah goats milked twice daily for seven consecutive days. The collected data were analyzed using simple linear regression with the assistance of SPSS software. The results showed a significant effect of milking time on milk production. Morning milking produced a higher volume of milk compared to afternoon milking with a sig value of 0.001. This is presumably due to a longer rest period at night and cooler environmental conditions in the morning. Hormonal factors, such as the hormone prolactin which influences the lactation process, also tend to be more active in the morning, which can increase milk production. It can be concluded that milking time affects the milk yield of crossbred etawah goats with morning milking being more effective in increasing production. Milking time is an important aspect in the lactation management of dairy goats. It is recommended that farmers optimize morning milking schedules to achieve maximum milk yield.